A quantitative-metallographic study of the sintering behaviour of dolomite - Yeprem, HA; Türedi, E; Karagöz, S (ELSEVIER SCIENCE INC, 2004)
Grain growth of the MgO phase during sintering of natural dolomite from Selcuklu-Konya in Turkey was studied in the temperature range 1600-1700 degreesC. For comparison purposes, iron oxide (98.66% mill scale) was added up to 1.5%. The compositions of the phases formed during sintering were studied using X-ray diffraction and scanning electron microscopy (SEM) with energy dispersive X-ray spectroscopy. Quantitative-metallographic analyses were performed on images taken by SEM. For the automatic image analysis of dolomite microstructures, material (atomic number) contrast with backscattered electrons (BSEs) was utilized because it yields higher phase contrast compared to secondary electrons (SEs). Iron oxide additions to dolomite result in dense dolomite structures at given sintering temperatures, where phases with low melting temperatures are developed. During liquid phase sintering, periclase is enriched with iron, which destabilizes the MgO phase. The relevant kinetic exponents for MgO in the natural doloma and 0.5% Fe2O3 added doloma were 6 and 2, and the activation energies were 108 and 243 kJ/mol, respectively. (C) 2004 Elsevier Inc. All rights reserved.
Keywords: dolomite; MgO; sintering; SEM; grain growth; GRAIN-GROWTH; Materials Science; Metallurgy & Metallurgical Engineering